Coating Persistent Luminescence Nanoparticles With Hydrophilic Polymers for in vivo Imaging - Liu, Jianhua; Kotrchová, Lenka; Lécuyer, Thomas; Corvis, Yohann; Seguin, Johanne; Mignet, Nathalie; Etrych, Tomáš; Scherman, Daniel; Randárová, Eva; Richard, Cyrille (Frontiers in Chemistry, 2020)
Persistent luminescence nanoparticles (PLNPs) are innovative nanomaterials highly useful for bioimaging applications. Indeed, due to their particular optical properties, i.e. the ability to store the excitation energy before slowly releasing it for a prolonged period of time, they allow in vivo imaging without auto-fluorescence and with a high target to background ratio. However, as for most nanoparticles (NPs), without any special surface coating, they are rapidly opsonised and captured by the liver after systemic injection into small animals. To overcome this issue and prolong nanoparticle circulation in the bloodstream, a new stealth strategy was developed by covering their surface with poly(N-2-hydroxypropyl)methacrylamide (pHPMA), a highly hydrophilic polymer widely used in nanomedicine. Preliminary in vivo imaging results demonstrated the possibility of pHPMA as an alternative strategy to cover ZnGa2O4:Cr NPs to delay their capture by the liver, thereby providing a new perspective for the formulation of stealth NPs.